2012
DOI: 10.1111/pbr.12013
|View full text |Cite
|
Sign up to set email alerts
|

Resistance breeding strategy for Stenocarpella maydis and Fusarium graminearum cob rots in tropical maize

Abstract: Maize cob rot caused by Fusarium graminearum and Stenocarpella maydis affects grain yield and quality. The objective of this study was to investigate the appropriateness of multiple infection as a selection and breeding strategy for multiple resistance to F. graminearum and S. maydis. Twelve tropical inbred lines with varying resistance to either or both pathogens were mated in a full diallel and the progeny and their parents evaluated for reaction to single or multiple infection. Under multiple inoculation, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…In this study, the small difference between the cultivars in relation to the incidence of S. maydis, observed in the healthy test, showed that despite the commercial corn hybrids being rated as to their resistance to stalk and ear rot (Casa et al, 2006;Denti et al, 2002), in practice little difference was observed between the strength of the materials considered susceptible (C1) and moderately resistant (C2), which in fact, according to Tembo et al (2013), is still a challenge for breeders. Based on the results of the assessment of incidence, it was also possible to infer that 24 hours of exposure to fungal colony would be enough for 50% of the seeds are infected, which can be useful not only for assessment of materials, but also to assess seed treatment, among other purposes.…”
Section: Eff Ect Of Incidence Of S Maydis In the Physiological Qualimentioning
confidence: 56%
“…In this study, the small difference between the cultivars in relation to the incidence of S. maydis, observed in the healthy test, showed that despite the commercial corn hybrids being rated as to their resistance to stalk and ear rot (Casa et al, 2006;Denti et al, 2002), in practice little difference was observed between the strength of the materials considered susceptible (C1) and moderately resistant (C2), which in fact, according to Tembo et al (2013), is still a challenge for breeders. Based on the results of the assessment of incidence, it was also possible to infer that 24 hours of exposure to fungal colony would be enough for 50% of the seeds are infected, which can be useful not only for assessment of materials, but also to assess seed treatment, among other purposes.…”
Section: Eff Ect Of Incidence Of S Maydis In the Physiological Qualimentioning
confidence: 56%
“…To curb this vice, deployment of resistant genotypes through breeding is the most cost effective way especially for the resource poor farmers in Zambia. However, resistance to S. maydis is greatly affected by underlying issues of gene interactions and the type of germplasm under study (Mukanga et al, 2011;Tembo et al, 2013). Identification of genotypes with stable resistance across locations can be utilized as the source of resistance in genotypic combinations (Tembo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, resistance to S. maydis is greatly affected by underlying issues of gene interactions and the type of germplasm under study (Mukanga et al, 2011;Tembo et al, 2013). Identification of genotypes with stable resistance across locations can be utilized as the source of resistance in genotypic combinations (Tembo et al, 2013). A higher number of resistant parental genotypes to S. maydis in mating combinations are likely to produce a larger proportion of stable resistant off-springs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations